A Secure Recommender System Model for Service Placement in Wireless Networks - Gashi, Luan; Luma, Artan; Snopçe, Halil; Januzaj, Ylber (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Edge or fog computing are being used to reduce latency between end devices and traditional cloud computing. The latest developments that have improved the hardware aspects of wireless sensors and mobile networks, gave the opportunity for other enhancements if such technologies are integrated between them. Regarding this enhanced heterogeneous environment, the approach of placing services needs to reconsider the security aspects. We have developed a baseline method of a solution which fulfills the cybersecurity requirements converging with the proposed multi-tier integrated model, that enhances the K-means algorithm with added processing steps supplying the criteria of the CIA triad.